Clinical-epidemiological profile of patients infected by COVID-19 in a municipality in southern Brazil (Research, Society and Development, 2023)
Objective: This study aims to identify the clinical-epidemiological profile of patients infected by COVID-19 in a municipality in southern Brazil from 2020 to 2022. Method: This is an observational, cross-sectional, retrospective, descriptive, quantitative study carried out with individuals infected with SARS-CoV-2 with notification registered in the database of a health service in the south of Santa Catarina. This infection is confirmed through laboratory tests (RT-PCR and/or antigen testing). Results: Females were the most affected (54.4%), the mean age was 42.21 years, with the most prevalent age group being 30-39 years (25.9%). The most used drug was azithromycin (13.2%). 27% had some pre-existing comorbidity, with systemic arterial hypertension being the underlying condition with the highest percentage (12.4%). The most prevalent symptoms were headache (47.1%), myalgia (43.9%) and cough (43.8%). 7.8% required hospitalization, 2.2% required the Intensive Care Unit, 98.4% were cured and 1.6% died. Conclusion: In the present study, the majority of COVID-19 infected patients were female, aged between 30-39 years. Males with preexisting comorbidities, within the age group 50-59 years, were more prevalent among those hospitalized, admission to the Intensive Care Unit and deaths.